(untitled) (Research, Society and Development, 2023)
Introduction: The quest for a perfect smile has been growing in contemporary society, leading many people to seek dental treatments to correct imperfections with composite resins. Objective: To present a clinical case of a 29-year-old male patient who sought dental treatment to improve the aesthetics of his anterior teeth, which had darkened color, color discrepancy, and irregular positioning of the dental elements. A treatment plan was developed that included dental bleaching, replacement of dental unit restorations, and the creation of composite resin veneers. The results were satisfactory, harmonizing the color, shape, and position of the teeth, providing a more harmonious smile. Conclusion: With the technological progress of adhesive systems, direct composite resin veneers are an excellent option for quick aesthetic corrections, with excellent cost-benefit and longevity, preserving healthy dental structure. However, the creation of composite resin veneers must be performed with the proper clinical evaluation of the patient, appropriate selection of color, and veneer creation technique, in order to obtain a satisfactory aesthetic and functional outcome.